Pengembangan E-Modul Pembelajaran Biologi Berbasis 3D Pageflip pada Materi Klasifikasi Makhluk Hidup untuk Siswa Kelas VII SMP: Development of E-Learning Module 3D Biology Based on Material Classification Pageflip Beings for Seventh Grade Students of SMP - Muhammad Khidayatullah Irfan; Upik Yelianti; Muhaimin Muhaimin (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2019)
Education is now entering an era that encourages the use of technology to support the learning process. One such technology is the 3D Pageflip media which combines interactive simulations with text, images, videos and animations. This study aims is to develop the product of 3D Pageflip based e-module about classification of living things, as well as to determine student’s perceptions of the e-modules. This development research uses the ADDIE’s model. The e-module of 3D Pageflip are validated by media expert and content expert. The results of the validation of material experts obtained a score about 87% which was categorized as "very valid", while media validation obtained the score about 80% in the "valid" category. The results of small group and large group trials obtained the scores 84% and 85% respectively, both were in the category of "very good". Furthermore, for the response of teachers are obtained the score about 88% with very good category. Overall the 3D Pageflip-based e-module is appropriate to be used as one of the learning materials on the classification of living things.